Barriers to the implementation of sexual and reproductive health education programmes in low-income and middle-income countries: a scoping review protocol - Mashora, Moreblessing Chipo (BMJ Open, 2019)
INTRODUCTION: Health education programmes (HEPs) have been associated with a number of benefits. These include providing individuals with information on matters related to their mental, social, physical as well as emotional health. HEPs also play a major role in preventing diseases and reducing the level of engagement of individuals in risky behaviours. While this is the case, there are barriers to the effective implementation of HEPs, especially in low-income and middle-income countries (LMICs) where resources are scarce. Available evidence has revealed socioeconomic challenges ranging from literacy issues, discomfort about issues of sexuality, and cultural barriers to financial constraints as key barriers to the implementation of sexual and reproductive health HEPs in LMICs. We will focus on HEPs related to sexual and reproductive health; all age groups will be considered with no restrictions on geographical setting nor model of HEP delivery. This review will map literature on the barriers to the effective implementation of HEPs in LMICs to guide future implementation research. METHODS: Arksey and O’Malley’s 2005 scoping methodological framework will act as the guide for this review. We will search the following electronic databases: EBSCOhost (Academic search complete, PsycINFO, Health Sources, CINAHL and MEDLINE with full text), Google Scholar, PubMed, SCOPUS, Science Direct and Web of Science. Grey literature from Mount Kenya University theses and dissertations, governments’ as well as international organisations’ reports, such as WHO, and reference lists of included studies will be searched for eligible studies. We will limit our search to publications from 1 January 2000 to 30 September 2019. Using thematic content analysis, we will employ NVivo V.12 to extract the relevant outcomes from the included articles. We will conduct a quality appraisal of the included articles using the mixed methods appraisal tool (MMAT) version 2018. ETHICS AND DISSEMINATION: No ethical approval is needed for the study as it will not include animal nor human participants. The results of the proposed scoping review will be disseminated electronically, in print and through conference presentation as well as at key stakeholder meetings.